Acquired partial lipodystrophy treated with poly-L-lactic acid and hyaluronic acid fillers: a case report. (19th May 2019) - Zhang, Amy J.; Moraites, Eleni; Goldfarb, Noah; Liszewski, Walter; Farah, Ronda S.
ABSTRACT: Acquired partial lipodystrophy (APL), also known as Barraquer-Simons syndrome, is a rare disorder characterized by progressive fat loss in the upper body. Use of poly-L-lactic acid and hyaluronic acid (HA) fillers for the treatment of APL is neither approved by the Food and Drug Administration nor described in the literature. Herein, we describe a case of APL that achieved significant improvement in facial volume following treatment with combination poly-L-lactic acid and HA fillers.